Physical and Biogeochemical Regionalization of the Southern Ocean and the CCAMLR Zone 48.1 - Testa, Giovanni; Piñones, Andrea; Castro, Leonardo R. (Frontiers in Marine Science, 2021)
The Southern Ocean (SO) plays a major role in the global climate, provides fisheries products and help the maintenance of biodiversity. The degree of correspondence between physical and biochemical spatial variability and regionalization were investigated by calculating the main physical factors that statistically explained the biochemical variability within the SO and the 48.1 zone of the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). The mean value of physical and biochemical variables was estimated during austral summer within a grid of 1° x 1° south of 50°S. The regionalization was developed using both non-hierarchical and hierarchical clustering method, whereas BIO-ENV package and distance-based redundancy analysis (db-RDA) were applied in order to calculate which physical factors primarily explained the biochemical spatial variability. A total of 12 physical and 18 biochemical significant clusters were identified for the SO (alpha: 0.05). The combination of bathymetry and sea ice coverage majorly explained biochemical variability (Spearman rank correlation coefficient: 0.68) and db-RDA indicated that physical variables expressed the 60.1% of biochemical variance. On the other hand, 14 physical and 16 biochemical significant clusters were identified for 48.1 CCAMLR zone. Bathymetry was the main factor explaining biochemical variability (Spearman coefficient: 0.81) and db-RDA analysis resulted in 77.1% of biochemical variance. The correspondence between physical and biochemical regions was higher for CCAMLR 48.1 zone with respect to the whole SO. Our results provide useful data for both SO and CCAMLR 48.1 zone management and ecosystem parametrization purpose.